2006
DOI: 10.1148/radiol.2413051534
|View full text |Cite
|
Sign up to set email alerts
|

Polyps: Linear and Volumetric Measurement at CT Colonography

Abstract: L(M3D) best approximated polyp size measurements at optical colonoscopy. Linear diameter calculated from automated volume measurements showed the smallest variation between supine and prone scans while avoiding observer variability and may be best for assessing polyp size changes with serial examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
1
19
1
Order By: Relevance
“…The experiments were performed in a fresh and unfi xed human colectomy specimen following subtotal colectomy from a patient with familial adenomatous polyposis. Similar results were obtained by Yeshwant et al ( 29 ), who found that manual 3D endoluminal polyp size measurements best approximated true size as determined at optical colonoscopy with a calibrated linear probe.…”
Section: Radiation Dosesupporting
confidence: 87%
See 2 more Smart Citations
“…The experiments were performed in a fresh and unfi xed human colectomy specimen following subtotal colectomy from a patient with familial adenomatous polyposis. Similar results were obtained by Yeshwant et al ( 29 ), who found that manual 3D endoluminal polyp size measurements best approximated true size as determined at optical colonoscopy with a calibrated linear probe.…”
Section: Radiation Dosesupporting
confidence: 87%
“…In a study of 251 polyps in which the authors compared CT colonography to optical colonoscopy with a linear probe, Yeshwant et al ( 29 ) found that to ensure identifi cation of all polyps measuring 10 mm at optical colonoscopy, all polyps measuring 8 mm or larger at CT colonography needed to be identifi ed. This result agreed with fi ndings in an observer performance study by Burling et al ( 30 ) using 28 observers; in that study, polyp sizes were generally underestimated by 2-3 mm compared with optical colonoscopy.…”
Section: Comparisons Of Ct Colonography To Endoscopic and Pathologic mentioning
confidence: 99%
See 1 more Smart Citation
“…While some data suggest that the sensitivity of CT colonography is high enough to warrant its use as a colorectal cancer screening strategy 10 , other data suggest that CT colonography, as it is currently most commonly performed, does not have adequate sensitivity 11,12 . Additionally, prognostic mathematical and cost-effectiveness models have identified other important factors that may ultimately determine the clinical and cost-effectiveness of CT colonography for colorectal neoplasia screening, including the following variables: 1) improvement in adherence to colorectal cancer screening based on availability of CT colonography, 2) duration of follow up interval after normal or equivocal CT colonography, 3) referral threshold for colonoscopic follow-up based on polyp size, and 4) the sensitivity and specificity of CT colonography for polyps ≥ 5mm and ≥1cm in size 13-17 . Though the sensitivity and specificity of CT colonography for colonic polyps at various size thresholds has received careful analysis in each of the published multicenter trials 10-12 , analysis of the measurement error associated with polyp size measurement has undergone limited study 10,[18][19][20] . Because CT colonography cannot evaluate polyp histology, the assessment of current and future risk for colorectal cancer (and patient management based on CT colonography findings) is fundamentally based on polyp size 21 .…”
Section: Introductionmentioning
confidence: 99%
“…However, current measurement of the single longest dimension of a polyp is subjective and has variations among radiologists. As evidence of the variability of manual linear measurement of polyps at CTC, studies reported interobserver and intraobserver variations between 16 to 40% (Yeshwant et al, 2006;Taylor et al, 2006;Jeong et al, 2008). As stated earlier, volume measurement could be more clinically informative than longest linear dimension, and this holds true in CTC.…”
Section: Introductionmentioning
confidence: 99%